A contextual game-based learning approach to improving students' inquiry-based learning performance in social studies courses. (February 2015) - Hwang, Gwo-Jen; Chiu, Li-Yu; Chen, Chih-Hung
Abstract: Inquiry-based learning, an effective instructional strategy, can be in the form of a problem or task for triggering student engagement. However, how to situate students in meaningful inquiry activities remains to be settled, especially for social studies courses. In this study, a contextual educational computer game is developed to improve students' learning performance based on an inquiry-based learning strategy. An experiment has been conducted on an elementary school social studies course to evaluate the effects of the proposed approach on the inquiry-based learning performances of students with different learning styles. The experimental results indicate that the proposed approach effectively enhanced the students' learning effects in terms of their learning achievement, learning motivation, satisfaction degree and flow state. Furthermore, it is also found that the proposed approach benefited the "active" learning style students more than the "reflective" style students in terms of learning achievement. This suggests the need to provide additional supports to students with particular learning styles in the future. Highlights: A contextual game based on an inquiry-based learning strategy was developed. The approach was applied to an elementary school social studies course. The approach improved the students' learning achievement. The approach improved the students' motivation, satisfaction degree and flow state. The approach benefited the "active" style students more than "reflective" style ones.